Assessing Covid-19 Threat Perceptions of Employees: A Generation Oriented Research in Turkiye - Osman Yalap; Mustafa Canbek (Istanbul Business Research)
Coronavirus threatens the physical and mental health of human beings throughout the world. Besides that, extraordinary measures, which are taken in order to protect the public health, have devastating effects on the global economy. In this context, it can be said that understanding the perceptions of employees who are surrounded by health and economic risks is crucial for the field of management. In the current study, it was investigated how Covid-19 threat perceptions of employees differ according to generation. With this purpose, data was collected from 535 public and private sector employees working in various provinces of Turkey. In order to analyze the collected data Independent sample t-test and one-way analysis of variance (ANOVA) were conducted. Findings indicated that Generation Z individuals are significantly different from other generations regarding Covid-19 threat perceptions. Generation Z perceives threats less than generation X and Y. The results of this research can be interpreted as that Generation Z employees feel more confident against the risks accompanying the coronavirus. In addition, statistically significant differences were found between some of the demographic characteristics of the participants and their perceptions of COVID-19 threats.